Implementasi Media Audio-Visual untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran SKI di MAN 2 Malang - Govern Shobach; Badrul Arifin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This research is motivated by the low student interest in learning Islamic Cultural History (SKI) at MAN 2 Malang, due to monotonous teaching methods and the dominance of textual materials. In response to technological advancement and the Merdeka Curriculum, this study explores the use of audio-visual media as a transformative approach in Islamic education. The aim is to evaluate its effectiveness in enhancing student engagement and learning outcomes. Employing a descriptive qualitative method, data were collected through participant observation, in-depth interviews, and documentation involving 2 SKI teachers and 30 twelfth-grade students. Data were analyzed using Miles and Huberman’s model—reduction, presentation, and conclusion drawing—supported by source triangulation. The findings indicate that audio-visual tools such as animated videos, digital slides, and interactive quizzes significantly improve student participation, motivation, and historical understanding through visual storytelling. This study offers a practical contribution by integrating technology into SKI learning, shifting it from passive to interactive. Despite positive outcomes, challenges such as infrastructure limitations, unequal digital access, and varying teacher digital literacy persist. The study suggests the need for structured training, equitable resource distribution, and curriculum alignment to ensure sustainable implementation. The novelty of this research lies in highlighting contextual application of media in faith-based education under the Merdeka Curriculum.